Peningkatan Kemampuan Membaca Siswa Kelas I SD melalui Media Buku Bergambar di Sanggar Bimbingan Sekolah Indonesia Kuala Lumpur - Sari, Fitria Puspita; Nasution, Wahidah; Kasmi, Hendra (Journal of Innovative and Creativity, 2026)
The study purpose was to improve the early reading skills of first-grade elementary school students through the use of illustrated book media. Early reading ability is a fundamental skill that must be mastered by students at the beginning level of education, yet many students still experience difficulties in recognizing letters, reading words, and understanding simple texts. Therefore, the use of engaging and visual learning media is considered important to support students’ reading development. Materials and methods. This study employed Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 15 first-grade students. Each cycle included four stages: planning, action, observation, and reflection. Data were collected through early reading tests, observation sheets of student and teacher activities, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques to measure improvement in students’ reading performance and learning activities. Results. The findings indicated that the use of illustrated book media improved students’ early reading skills. In Cycle I, the percentage of learning mastery reached 60%, which was categorized as fair. After improvements in teaching strategies and media utilization in Cycle II, the percentage increased to 80%, categorized as good. Additionally, students showed increased participation, motivation, and attention during the learning process Conclusions. The study concludes that illustrated book media is effective in improving early reading skills of first-grade elementary school students. The media not only enhances reading achievement but also increases students’ engagement and interest in learning.